2005
DOI: 10.1136/bmj.38334.591586.82
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of β lactam antibiotics compared with antibiotics active against atypical pathogens in non-severe community acquired pneumonia: meta-analysis

Abstract: Objective To systematically compare lactam antibiotics with antibiotics active against atypical pathogens in the management of community acquired pneumonia. Data sources Medline, Embase, Cochrane register of controlled trials, international conference proceedings, drug registration authorities, and pharmaceutical companies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
90
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 36 publications
2
90
1
7
Order By: Relevance
“…Previous meta-analyses, although of high quality, have addressed somewhat different questions using different inclusion criteria [6,7]. BJERRE et al [6], although limiting their analysis to studies of outpatients, included studies in which all participants received therapy with atypical activity, making it impossible to address whether or not atypical coverage is helpful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous meta-analyses, although of high quality, have addressed somewhat different questions using different inclusion criteria [6,7]. BJERRE et al [6], although limiting their analysis to studies of outpatients, included studies in which all participants received therapy with atypical activity, making it impossible to address whether or not atypical coverage is helpful.…”
Section: Discussionmentioning
confidence: 99%
“…To the meta-analysis of BJERRE et al [6], the present study, therefore, adds an analysis of almost 1,200 patients in order to assess whether or not atypical therapy is useful in OCAP, an analysis of an additional 1,200 patients comparing macrolide versus fluoroquinolone therapy and analyses comparing other drug classes. MILLS et al [7] apparently included both in-patient and outpatient studies in their meta-analysis, and focused exclusively on whether atypical coverage is beneficial. Data are presented as n or n (%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and C. pneumoniae were both found in three patients, which might explain why regimens covering these organisms did not substantially affect the outcome in the current study. Moreover, evidence is lacking that clinical outcomes are improved by using antibiotics that are active against atypical pathogens, at least in nonsevere CAP [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mills et al showed no advantage of antibiotics active against atypical pathogens over BL antibiotics in nonsevere CAP, again with the exception of patients with Legionella pneumonia (16).…”
Section: Discussionmentioning
confidence: 99%